GENDER FLUIDITY OF DSD CHARACTERS IN MIZUSHIRO SETONA'S HOUKAGO HOKENSHITSU MANGA - Rahman, Aulia; Rachmidian, Rahayu (Program Studi Sastra Jepang Fakultas Ilmu Budaya Universitas Bung Hatta, 2025)
This research is entitled